Duolingo and Hello Talk Apps in Increasing Students Confidence and Motivation in Speaking English - Yulianti, Putri; Hidayati; Irwandi; Dian Eka Mayasari; Bq Desi Milandari (Universitas Pendidikan Ganesha, 2025)
Low student motivation in English speaking skills highlights the need for technology-based learning innovations. This study aims to evaluate the effectiveness of Duolingo and Hello Talk applications in increasing students’ confidence and motivation. The method used in this study is quantitative. The subjects were 20 students from class A and 20 students from class B in Junior High School, selected using convenience sampling. Data were collected through pre-test and post-test administration after the treatment using Duolingo and Hello Talk applications. The research instruments consisted of a questionnaire and a test. Data were analyzed using paired t-test to compare the mean scores before and after the treatment in both groups. The analysis showed that students achieved a higher average score using Duolingo (7533.3) compared to Hello Talk (6966.7), with a statistically significant difference (p = 0.001) and a medium to large effect size (Cohen’s d = 0.789). A moderately strong positive correlation (r = 0.660) between the results of both applications indicates that they complement each other in supporting the learning process. It can be concluded that Duolingo is more effective in consistently increasing student motivation through structured practice, while Hello Talk contributes to building confidence through authentic social interaction. The results of this study imply the importance of integrating both applications into English learning strategies, particularly in developing students’ speaking skills more comprehensively and adaptively in accordance with 21st-century learning needs.